PENGARUH KOMPENSASI DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PRIMER KOPERASI KARYAWAN KRAKATAU STEEL - Rani Sri Sumarsih; Fatari Fatari (Jurnal Valuasi: Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2023)
This study aims to determine the effect of compensation and work motivation on employee performance in Krakatau Steel Primary Cooperative Employees partially and simultaneously. This study uses quantitative research with a survey method that takes samples from a population and uses a questionnaire as a means of collecting primary data with a Likert scale. This study uses a multiple correlation model which is included in correlation research to determine the level of relationship / influence between two or more variables. The population in this study were all 60 employees. The results of the research hypothesis testing Compensation on Employee Performance obtained tcount > ttable (4.030 > 2.002) and a significant value of α (0.00 <0.05). Work motivation on employee performance obtained tcount > ttable (2.761 > 2.002) and a significant value of α (0.008 <0.05). Compensation and Work Motivation on Employee Performance obtained Fcount > Ftable or 12.205 > 3.16 and a significant value of α (0.00 <0.05). The conclusion from this study is that there is an effect of compensation and motivation on employee performance either partially or simultaneously.